Neuronal calcium sensors and synaptic plasticity. (19th November 2009) - Amici, Mascia; Doherty, Andrew; Jo, Jihoon; Jane, David; Cho, Kwangwook; Collingridge, Graham; Dargan, Sheila
Abstract : Calcium entry plays a major role in the induction of several forms of synaptic plasticity in different areas of the central nervous system. The spatiotemporal aspects of these calcium signals can determine the type of synaptic plasticity induced, e.g. LTP (long-term potentiation) or LTD (long-term depression). A vast amount of research has been conducted to identify the molecular and cellular signalling pathways underlying LTP and LTD, but many components remain to be identified. Calcium sensor proteins are thought to play an essential role in regulating the initial part of synaptic plasticity signalling pathways. However, there is still a significant gap in knowledge, and it is only recently that evidence for the importance of members of the NCS (neuronal calcium sensor) protein family has started to emerge. The present minireview aims to bring together evidence supporting a role for NCS proteins in plasticity, focusing on emerging roles of NCS-1 and hippocalcin.